How Situationism Impacts the Goals of Character Education - Miller, Christian B. (Ethical theory and moral practice, 2024)
The focus of this special issue is on moral psychology and the goals of moral education. My focus will be considerably narrower in addressing the following question: In light of the situationist movement in psychology and philosophy, what should be the goal(s) of character education? The main conclusion will be that the central goal of character education should be modified in a certain way to make it more empirically informed. But not to worry, as this modification should be amenable to most contemporary supporters of character education.